Pengaruh Kualitas Pelayanan Dan Kepuasan Terhadap Loyalitas Pelanggan Wifi Indihome PT. Telekomunikasi Indonesia Wilayah Sumatera Selatan - Rohmial , Rohmial (Catholic University Musi Charitas, 2022)
The purpose of this study to examine the effect of service quality and satisfaction on customer loyalty P.T. IndiHome. The test was conducted on 83 people with non-probability sampling technique, while the sampling used incidental sampling using the Slovin formula. Calculations The analysis technique was performed using normality test, t test, F test, multiple linear regression and determination test. The results of this study indicate the quality of service and satisfaction is good but still need to improve the speed and accuracy in handling customer complaints. Simultaneously service quality and satisfaction have a positive and significant effect on customer loyalty at PT Telekomunikasi Indonesia (WITEL) South Sumatra, where the calculated F value with a significant value . Keywords: Service Quality, Satisfaction, Customer Loyalty.